3 - Citizenship and Partitioned People in East Africa: The Case of the Wamaasai*: 10.4314/ad.v28i1.22169 - Chachage, Chachage S. L. (Africa Development, 2022)
This paper focuses on the issues of globalization and citizenship. It takes to task the various ways in which the issue of African integration has been conceptual ized, by bringing in the question of the partitioned communities. It examines the situation of a partitioned people in East Africa, the Wamaasai, as social actors capable of making interventions and reconstructing other organizational capaci ties, including states, which can effectively deal with the global economy for their mutual survival. Moreover, it deals with the differentials in access to land and natural resources in the context of gender, class, race, age, ethnic, national, and other forms of imbalances, while at the same time problematizing citizen ship in the African and global context. The Wamaasai people, cut nearly in half by the Kenya-Tanzania border live in a situation whereby boundaries were drawn across well established lines of communication including, in every sense, an active sense of community based on traditions, common ancestry, kinship ties, shared socio-political institutions and economic resources. These pastoralist groups, in both countries, have been facing harsh conditions because of being deprived of their lands and resources by their respective states, which have al ienated them for agriculture and tourism. They have also been persecuted be cause of their resistance to 'modernity'. The paper is historical in its focus and analysis, with the aim to find ways of dealing with the problems facing the border/partitioned people through Pan-Africanist solutions.